Answer:
x²-12x+36
Step-by-step explanation:
an expression in the form (a-b)² is expanded to the form a²-2ab+b²
you can also expand it to (x-6)×(x-6) then multiply the first term by the first the outer term by the outer term the inner term by the inner term and the last term by the last term (foil)
the first terms are x and x = x² the outer terms are x and -6 = -6x the inner terms are also x and -6 = -6x
the last terms are 6 and 6 = 36
adding all the four products =
x²-12x+36
If this is a combination problem, 325 choose 1, anytime you have a choose 1, the answer it the n, so 325 is the answer.
-9 × 3 - 4² = -27 - 16 = -43
3² + 2² = 9 + 4 = 13
(-9 × 3 - 4²)/(3² + 2²) = -43/13 = -3 4/13
Answer:
22
Step-by-step explanation:
We can use the order of operations (PEMDAS), to solve this equation.
We must first multiply and divide, and order. This means we divide 12 by 3 and get 4, then multiply that by 2 and get 8. (30-12÷3×2,30-4×2,30-8). Now we just subtract 8 from 30 and get 22 as our answer.